Bioconversion of spent coffee grounds to prebiotic mannooligosaccharides – an example of biocatalysis in biorefinery. Issue 6 (26th January 2023) - Magengelele, Mihle; Malgas, Samkelo; Pletschke, Brett I.
Abstract : Spent coffee grounds can be bioconverted via Man26A to prebiotic mannooligosaccharides; this is an example of biocatalysis in the biorefinery. Abstract : Spent coffee ground (SCG), an agro-industrial waste, have a high content of polysaccharides such as mannan, making it ideal for utilisation for the production of nutraceutical oligosaccharides. Recently, there has been growing interest in the production of mannooligosaccharides (MOS) for health promotion in humans and animals. MOS are reported to exhibit various bioactive properties, including prebiotic and antioxidant activity. In this study, SCG was Vivinal pretreated using NaOH, characterized and hydrolysed using a Bacillus sp. derived endo -β-1, 4-mannanase, Man26A, for MOS production. Structural analyses using Fourier-transform infrared spectroscopy (FT-IR) and thermogravimetric analysis (TGA) were conducted to assess the efficacy of the pretreatment. Lignin removal by the pretreatment from SCG was clearly shown by TGA. FT-IR, on the other hand, showed the presence of α-linked d -galactopyranoside (812 cm −1 ) and β-linked d -mannopyranoside residues (817 cm −1 ) in both SCG samples, signifying the presence of mannan. Hydrolysis of pretreated SCG by Man26A produced mannobiose and mannotriose as the main MOS products. The effect of simulated gastric conditions on the MOS was investigated and showed this product to be suitable for oral administration. Finally, the prebiotic effect of the MOS on the growth of selected beneficial bacteria was investigated in vitro ; showing that it enhanced Lactobacillus bulgaricus, Bacillus subtilis and Streptococcus thermophilus growth. These findings suggest that SCG is a viable source for the production of MOS which can be orally administered as prebiotics for effecting luxuriant growth of probiotic bacteria in the host's digestive tract, leading to a good health status.